MICROTHERMOMETRIC AND RAMAN SPECTROSCOPIC DETECTION LIMITS OF CO2 IN FLUID INCLUSIONS AND THE RAMAN SPECTROSCOPIC CHARACTERIZATION OF CO2 - Rosso K.M.; Bodnar R.J. (My University, 1995)
In many geologic environments, dominantly aqueous solutions contain low concentrations of CO2. At ambient temperature, the typical phase assemblage in fluid inclusions which trap these solutions, consists of a CO2-rich vapor (where PCO2 ~ Pinternal) and an aqueous phase containing dissolved salts and CO2. In this study, the CO2 detection limits (DLs) using microthermometry and Raman spectroscopy are established in terms of PCO2 using synthetic H2O-CO2 inclusions of known composition. The purpose of the microthermometric experiments was to identify the diagnostic CO2 phase changes and determine the quantity of CO2 necessary to result in observable solid CO2 melting. The results of these experiments show that an observable solid CO2 melting event in liquid-rich aqueous inclusions requires PCO2 =< 45 bars at 25°C.The Raman spectroscopic detection limits were investigated using a multichannel Raman spectrometer. The CO2 DLs were obtained by determining signal-to-noise ratios for both the upper and lower ν1-2ν2 bands as a function of CO2 pressure (5-60 bars) over a range of integration times and incident laser power. The resulting CO2 DLs are on the order of 1 bar for the instrument used.The band splitting of the ν1-2ν2 diad as a function of CO2 pressure, converted to CO2 density, was measured up to 500 bars at ambient temperature. The results are given in terms of the frequency separation between the upper and lower bands and are compared to results of previous studies. An analysis of the estimated errors indicates that the technique can be used to determine CO2 densities in fluid inclusions containing a homogeneous, free CO2 phase to a precision of approximately +/-0.02 g/cm3.The temperature dependence of the intensity ratio of the hot bands to the ν1-2ν2 diad was measured from 270-315 K. The close agreement between the calculated and observed results indicates that laser induced sample heating is not significant. The intensity ratio can be used to estimate the CO2 temperature and, combined with the Raman density determination, allows calculation of the CO2 pressure.